As possibilidades e limites do benefício de prestação continuada para os beneficiários do município de Patos/PB - Lima, Virgínia Helena Serrano Paulino (2015)
This dissertation investigates the possibilities and limitations of BPC provision for the beneficiaries of the Municipality of Patos / PB. Assuming that this benefit is in the context of the Brazilian social security, it was necessary to historically contextualize its trajectory from the consolidation of social policies in the neoliberal hegemony development context that caused repercussions in shaping social policies, mainly for social assistance. The object of this study is that the BPC is constitutionally guaranteed and provide the minimum monthly wage to the disabled and the elderly who prove to have means to provide for their own support or having it provided by his family. The territory of the research took place in the city of Patos / PB, for he entered the sample survey entitled "Social Protection of the Family" held at the state level, through the Center for Studies and Research in Social Policy, linked to the Graduate Program in Social Service, Federal University of Paraíba, on the occasion of this research were applied 2,095 questionnaires, involving beneficiary families of income transfer programs, Bolsa Família and Benefit of Continuous Cash. In this study we analyzed the 39 interviews conducted in Patos, only GCP, 21 of these have been the beneficiary families of the disabled BPC and 18 with the beneficiary families BPC Elderly. We characterize the beneficiary families as family composition, gender, education and occupational status, we find that both families have similar characteristics are poor, have little education and are mostly unemployed. In an attempt to elucidate the process of accessibility we have seen that most of them learned of registration through friends and relatives about where registered most reveleou that the INSS agency also inquired about the use of CRAS services we saw that the large proportion of respondents did not know and does not use the services offered by it. We seek also know the importance of it to these families, it was found that the monetary value is directed to food and medicines meeting the most basic needs of individuals. We find that their access criteria are strict, the articulation of it with social assistance services are incipient, but for those who can access it saw that despite being an individual character of the benefit it brings repercussions for the whole family.